Intestinal Microbial Ecology in Premature Infants Assessed with Non–Culture-Based Techniques - Mshvildadze, Maka; Neu, Josef; Shuster, Jonathan; Theriaque, Douglas; Li, Nan; Mai, Volker (The Journal of pediatrics, 2010)
To use high throughput techniques to analyze intestinal microbial ecology in premature neonates, who are highly susceptible to perturbations of the luminal environment associated with necrotizing enterocolitis (NEC) and late-onset sepsis. With non–culture-based techniques, we evaluated intestinal microbiota shortly after birth and during hospitalization in 23 neonates born at 23 to 32 weeks gestational age. Microbiota compositions were compared in 6 preterm infants in whom NEC, signs of systemic inflammation, or both developed with matched control subjects by using 16S ribosomal RNA pyrosequencing. Microbial DNA was detected in meconium, suggesting an intrauterine origin. Differences in diversity were detected in infants whose mothers intended to breast feed ( P = .03), babies born to mothers with chorioamnionitis ( P = .06), and in babies born at <30 weeks gestation ( P = .03). A 16S ribosomal RNA sequence analysis detected Citrobacter-like sequences only in cases with NEC (3 of 4) and an increased frequency of Enterococcus-like sequences in cases and Klebsiella in control subjects ( P = .06). The overall microbiota profiles in cases with NEC were not distinguishable from that in control subjects. Microbial DNA in meconium of premature infants suggests prenatal influences.